Children’s narrative comprehension: effects of working memory and sustained attention - Formoso, Jesica (2023)
Text comprehension involves the construction of a coherent mental representation. For children, this is a cognitively demanding task. The purpose of this study is to analyze the role of working memory (WM) and sustained attention (SA) in the comprehension of narratives in 5- and 6-year-old children. For this, 100 children were administered two WM tasks and one SA. To assess comprehension, they were asked 18 questions of literal and inferential content about three stories previously narrated by a professional storyteller. A correlation analysis showed that literal comprehension associated with forward digit span (Rho = 0.37), backward digit span (Rho = 0.37), and the SA task (Rho = −0.37). Inferences correlated with forward digit span (Rho = .36), backward digit span (Rho = 0.46), and the SA task(Rho = −0.37). A comparison analysis indicated significant differences between 5- and 6-year-olds in SA (t(98) = 3.08, SEM = 5.41,p < .01), literal comprehension (t(98) = 4.05,p < .001), and inferences (U = 750.50,p < .001), but not in forward digit span(t(98) = 1.43, p = .16) and backward digit span(U = 1043.50, p = .14). Finally, a path analysis was conducted with age as an independent variable, comprehension as the dependent variable, and WM and SA as mediating variables, being comprehension, a latent factor formed by literal information and inferences, and WManother latent factor formed by forwarding dig-its and backward digits span. The path analysis showed a good fit of the data to the model(c2(1.93, p = .86; AGFI = .97, CFI = .99, TLI = .99, RMSEA = .00). The analysis showed that age had a significant effect on all measures except WM, and both WM and SA play a role in comprehension. This suggests that, in 5 and 6-year-olds, age has an effect on the comprehension of general information and the ability to generate inferences, but this effect is mediated, in part, by the child’s ability to SA on the narration and to temporarily store the information received while listening to it.